Modular Electrode Array for Multi‐site Extracellular Recordings from Brains of Freely Moving Rodents. Issue 5 (10th May 2022) - Mohapatra, Alok Nath; Netser, Shai; Wagner, Shlomo
Abstract: Multi‐site extracellular recordings from awake, freely moving rodents are an insightful technique that allows deduction of the dynamics of neural activity within a network of brain regions. Multiple advances in the design and materials of recording setups are available in the literature. However, most of these designs require several skill sets to assemble the electrodes and are expensive. Here, we explain in detail a custom design to build a multi‐site (16 sites) electrode array (EA) and record extracellular electrical signals (local field potential and multi‐unit spiking activity) at variable depths in freely behaving rodents. This EA weighs ∼3.0 g and costs less than $30. It provides mesoscopic neural activity maps (at millimeter scale) at low spatial resolution, thus enabling the experimenting group to further target specific regions with more expensive high‐density probes at the resolution of an individual neuron. The article outlines the processes of building and implanting the array and recording neural activity during a behavior task. We also highlight the limitations of our design and the necessary steps to troubleshoot common issues faced during the initial implementation of the protocols. Finally, we explain the specific data one would obtain while using the probes during social interactions between rodents. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Preparation of the electrode array Basic Protocol 2 : Surgical implantation of the electrode array Basic Protocol 3 : Recording of neural activity from the electrode array while a mouse performs social investigation of a novel conspecific Basic Protocol 4 : Histology and electrode registration